2008
DOI: 10.1111/j.1745-4557.2008.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPID MESOCARP CELL ELONGATION ENHANCES GUMMING SYNDROME IN JAPANESE APRICOT (PRUNUS MUME SIEB. ET ZUCC.) FRUIT

Abstract: Japanese apricot (Prunus mume Sieb. et Zucc.) 'Benisashi' fruit tends to show the physiological disorder of a gumming syndrome, while the fruit known as 'Nanko' rarely show this. The accumulated gum becomes a solid gel during the processing period and the commercial value of the mume pickle is consequently decreased. In the present experiment, gum accumulation in the mesocarp tissue and the cell size of the tissue during fruit growth were observed in the two cultivars. In mid-May, the initiation of the gum duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In a previous study, we reported that 'Benisashi' fruit grew more rapidly than 'Nanko' fruit during the rapid mesocarp development stage, just before the fruit ripened (stage III), due to explosive mesocarp cell elongation close to the endocarp. The uncoordinated cell growth between the inner and outer mesocarp of 'Benisashi' fruit may cause cracks at junction areas of inner and outer mesocarp cells, leading to the accumulation of gum in the cracks; however, this phenomenon does not occur in 'Nanko' fruit (Matsumoto et al, 2008). The rapid mesocarp development stage usually starts in the first ten days of May.…”
Section: Treatment Of Chemicalsmentioning
confidence: 98%
See 4 more Smart Citations
“…In a previous study, we reported that 'Benisashi' fruit grew more rapidly than 'Nanko' fruit during the rapid mesocarp development stage, just before the fruit ripened (stage III), due to explosive mesocarp cell elongation close to the endocarp. The uncoordinated cell growth between the inner and outer mesocarp of 'Benisashi' fruit may cause cracks at junction areas of inner and outer mesocarp cells, leading to the accumulation of gum in the cracks; however, this phenomenon does not occur in 'Nanko' fruit (Matsumoto et al, 2008). The rapid mesocarp development stage usually starts in the first ten days of May.…”
Section: Treatment Of Chemicalsmentioning
confidence: 98%
“…On the other hand, 'Nanko' fruit does not develop gumming syndrome until fruit maturation (Yamaguchi et al, 2004). A previous report (Matsumoto et al, 2008) indicated that, in mid-May, gum duct initiation and plant gum accumulation could be observed in vascular bundles in the mesocarp tissue of both 'Benisashi' and 'Nanko' Japanese apricot fruit; however, although 'Nanko' fruit does not develop a gum lump that is visible to the naked eye until the mature stage, 'Benisashi' fruit develops clearly visible gum lumps. Morrison and Polito (1985) reported that a gum duct forms naturally in many kinds of cultivated Prunus species; however, gum production is intensified after mechanical or insect damage, pathogenic infection, or 274 exposure to ethylene-producing chemicals (Bukovac, 1979;Martin and Nelson, 1969;Morrison et al, 1987;Olien and Bukovac, 1982;Saniewski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations